2019
DOI: 10.1007/s40271-019-00372-z
|View full text |Cite
|
Sign up to set email alerts
|

Support Tools for Preference-Sensitive Decisions in Healthcare: Where Are We? Where Do We Go? How Do We Get There?

Abstract: Understanding and respecting patients' values, preferences and expressed needs are the foundation of patient-centered care." Harvey Picker [1]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This approach, where clinicians and patients collaborate in making clinical plans, is a key component to delivering personcentered care. [2][3][4][5] Patients who are more activated (ie, view themselves as active managers of their health and healthcare) have been shown to have better outcomes and care experiences, and a key measure of patient activation is their involvement in decision making. 6 A recent Cochrane review found that patients exposed to decision aids used for shared decision making felt more knowledgeable of risks and benefits, better informed, and clearer about their values.…”
Section: Introductionmentioning
confidence: 99%
“…This approach, where clinicians and patients collaborate in making clinical plans, is a key component to delivering personcentered care. [2][3][4][5] Patients who are more activated (ie, view themselves as active managers of their health and healthcare) have been shown to have better outcomes and care experiences, and a key measure of patient activation is their involvement in decision making. 6 A recent Cochrane review found that patients exposed to decision aids used for shared decision making felt more knowledgeable of risks and benefits, better informed, and clearer about their values.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this approach has applicability to both chronic and acute conditions. While the options for varying preferences in clinical practice may be more limited for acute or time-limited conditions as compared to chronic conditions, acute conditions are still preference-sensitive, i.e., requiring some form of trading between risks and benefits as well as other aspects of care that contribute to overall quality of care [40][41][42]. Because the opportunity to incorporate patient preferences for those other aspects of quality care for acute conditions is limited at the point of care, then one may argue that using preference methods to inform the design of treatments for acute conditions may be more pertinent than chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Building on this appropriateness research, another related application of PROMs at the micro level is the role of PROMs to inform setting realistic expectations for patients, and promoting shared decision-making with their care provider [ 21 ]. We evaluated whether routinely collected pre- and post-TKA PROMs could be integrated into a patient decision aid to better inform these appropriateness criteria in a randomized controlled trial with a primary outcome measure of decision quality [ 22 ].…”
Section: Application Of Proms In Routine Clinical Practice and Health Care Servicesmentioning
confidence: 99%